2009
DOI: 10.1016/j.jneuroim.2009.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib mesylate ameliorates the dystrophic phenotype in exercised mdx mice

Abstract: Myofiber degeneration, inflammation, and fibrosis are remarkable features of Duchenne muscular dystrophy. We hypothesized that the administration of imatinib mesylate, an inhibitor of tyrosine kinase and TGF-beta pro-fibrogenic activity, could improve the muscular conditions in mdx mice. Four-week old mdx mice were treated and exercised for 6 weeks. Gastrocnemius and diaphragm histopathology, strength, creatine kinase, and cytokine levels were evaluated. The treated group presented increased muscular strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 50 publications
(60 reference statements)
2
23
0
1
Order By: Relevance
“…Such effects appear to depend on the inhibition exerted by the drug on the activation of both c-Abl and PDGFR on both peritoneal macrophages and muscleresident fibroblasts (Huang et al, 2009). Similar observations have been independently reported by another group (Bizario et al, 2009). Both reports suggest that treatment with IM exerts a marked anti-inflammatory effect, lowering the levels of proinflammatory cytokines.…”
Section: Wwwintechopencomsupporting
confidence: 92%
See 1 more Smart Citation
“…Such effects appear to depend on the inhibition exerted by the drug on the activation of both c-Abl and PDGFR on both peritoneal macrophages and muscleresident fibroblasts (Huang et al, 2009). Similar observations have been independently reported by another group (Bizario et al, 2009). Both reports suggest that treatment with IM exerts a marked anti-inflammatory effect, lowering the levels of proinflammatory cytokines.…”
Section: Wwwintechopencomsupporting
confidence: 92%
“…The results show that while able to improve muscle phenotype in mdx mice (Bizario et al, 2009;Huang et al, 2009), IM is ineffective in preventing muscle wasting in tumor-bearing animals, although it likely exert an anti-inflammatory action, as shown by the protection against spleen hypertrophy. These observations may suggest that the tyrosine kinases blocked by IM might not be involved in the pathogenesis of muscle wasting in cancer cachexia.…”
Section: Wwwintechopencommentioning
confidence: 84%
“…Treatment of rats with imatinib after bleomycin administration results in a strong reduction in TGF-β1 gene expression [35]. Bizario et al [36] showed that imatinib treatment reduces the levels of TGF-β cytokine and mRNA in mdx mice. In a murine lupus model, renal TGF-β expression was reduced by imatinib treatment [37].…”
Section: Discussionmentioning
confidence: 99%
“…It is an orally administered drug with antineoplastic, anti-inflammatory and antifibrotic capabilities that has been shown to be well tolerated by adults in the treatment of many cancers [312,313]. Two studies in mdx mice have demonstrated that Imatinib could be beneficial in reducing necrosis, inflammation, fibrosis, and improving muscle strength [249,314].…”
Section: Tgf-mentioning
confidence: 99%